2022
DOI: 10.1002/ams2.724
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory distress syndrome due to inhalation of acryloyl chloride

Abstract: Background Acryloyl chloride is a highly toxic volatile liquid that can cause pulmonary edema. However, no sufficient treatment reports have been published to date. Here, we report a case of acute respiratory distress syndrome (ARDS) caused by acryloyl chloride inhalation. Case presentation The patient was a 36‐year‐old man with accidental exposure to acryloyl chloride. The patient had dyspnea and wet cough, with approximately 88% percutaneous oxygen saturation at room … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Our entire research team was waiting outside the emergency ward, and in the meantime, I began searching for previously published cases involving acryloyl chloride accidents. Shima et al reported “acute respiratory distress (ARDS) syndrome” due to acryloyl chloride inhalation in a 36 year-old man who was accidentally exposed to the acryloyl chloride . He was admitted to the intensive care unit (ICU) after being diagnosed with ARDS.…”
Section: Post-accident Analysis (Post-accident Incidences Diagnosis A...mentioning
confidence: 99%
See 4 more Smart Citations
“…Our entire research team was waiting outside the emergency ward, and in the meantime, I began searching for previously published cases involving acryloyl chloride accidents. Shima et al reported “acute respiratory distress (ARDS) syndrome” due to acryloyl chloride inhalation in a 36 year-old man who was accidentally exposed to the acryloyl chloride . He was admitted to the intensive care unit (ICU) after being diagnosed with ARDS.…”
Section: Post-accident Analysis (Post-accident Incidences Diagnosis A...mentioning
confidence: 99%
“…Due to the possibility of a delayed exacerbation, he was later switched to methylprednisolone. The patient’s oxygenation gradually improved, and he was discharged on the eighth day of his hospitalization . I became more concerned after reading the Lau et al report, in which he reported three cases of direct inhalation of acryloyl chloride (96%) and methacrylic anhydride (94%) .…”
Section: Post-accident Analysis (Post-accident Incidences Diagnosis A...mentioning
confidence: 99%
See 3 more Smart Citations